PEMANFAATAN KOLOSTRUM SAPI DALAM PEMBUATAN PERMEN KARAMEL SUSU SEBAGAI OLEH-OLEH WISATAWAN LEMBANG - Sonny Pratama Mandara; Sara Rabasari (Akademi Pariwisata NHI Bandung, 2021)
This study aims to determine the taste, calculation of production costs, nutritional information, and shelf life of Milk Caramel Candy using Cow Colostrum with Milk Caramel Candy made from cow's milk. Food diversification made from cow's milk colostrum can minimize the loss value of cow's milk colostrum, which is mostly discarded by processing it into caramel candy, an alternative souvenir for Lembang tourists. The collection method used is the experimental method. Data collection techniques were carried out through product experiments, distributing questionnaires, and observing. While the data analysis technique using a hedonic scale. Based on the results of the study, it can be seen that Professional Panellists and Consumer Panellists prefer the color, aroma, taste, and texture of Experimental Milk Caramel Candy, Experimental Milk Caramel Candy contains 27.7% carbohydrates, 0.65% fat, 1.4% protein higher than Comparative Milk Caramel Candy. Meanwhile, the calorie content of the Comparative Milk Caramel Candy was 0.03% higher than the Experimental Milk Caramel Candy. So that the Experimental Milk Caramel Candy is good for consumption as a nutritious snack for tourists while traveling in Lembang, the Experimental Milk Caramel Candy, the author spends Rp. 9,335, - with a packaging fee of Rp. 50,-, Experimental Milk Caramel Candy can last up to 3 (three) weeks at normal room temperature by using closed packaging and in the refrigerator. Suggestions given for problem-solving are: 1) Presenting other flavor variants so that they become an attraction for consumers or tourists; 2) Create a new variant by replacing one of the ingredients in the recipe used to make Experimental Milk Caramel Candy with other ingredients such as using Stevia Sugar in the hope of expanding the market reach and thereby attracting consumers who cannot consume sugar; 3) To develop further research on the use of Cow Colostrum for other processed products considering the nutritional content is better than Cow's Milk so that it becomes another new product variant, and 4) Further research is conducted to increase the shelf life of the product for a longer period.